Impact of 5-h phase advance on sleep architecture and physical performance in athletes - Petit, E.; Mougin, F.; Bourdin, H.; Tio, G.; Haffen, E. (Applied Physiology, Nutrition, and Metabolism, 2014)
Travel across time zones causes jet lag and is accompanied by deleterious effects on sleep and performance in athletes. These poor performances have been evaluated in field studies but not in laboratory conditions. The purpose of this study was to evaluate, in athletes, the impact of 5-h phase advance on the architecture of sleep and physical performances (Wingate test). In a sleep laboratory, 16 male athletes (age: 22.2 ± 1.7 years, height: 178.3 ± 5.6 cm, body mass: 73.6 ± 7.9 kg) spent 1 night in baseline condition and 2 nights, 1 week apart, in phase shift condition recorded by electroencephalography to calculate sleep architecture variables. For these last 2 nights, the clock was advanced by 5 h. Core body temperature rhythm was assessed continuously. The first night with phase advance decreased total sleep time, sleep efficiency, sleep onset latency, stage 2 of nonrapid eye movement (N2), and rapid eye movement (REM) sleep compared with baseline condition, whereas the second night decreased N2 and increased slow-wave sleep and REM, thus improving the quality of sleep. After phase advance, mean power improved, which resulted in higher lactatemia. Acrophase and bathyphase of temperature occurred earlier and amplitude decreased in phase advance but the period was not modified. These results suggest that a simulated phase shift contributed to the changes in sleep architecture, but did not significantly impair physical performances in relation with early phase adjustment of temperature to the new local time.